Light-gated amorphous carbon memristors with indium-free transparent electrodes. (November 2019) - Murdoch, B.J.; Raeber, T.J.; Zhao, Z.C.; Barlow, A.J.; McKenzie, D.R.; McCulloch, D.G.; Partridge, J.G.
Abstract: Amorphous carbon-based memristors with transparent conductive electrodes can be programmed both optically and electronically. We demonstrate neuromorphic logic and memory functions using light-gated amorphous carbon (a-C) memristors with indium-free transparent electrodes. The devices consist of insulating tetrahedral a-C layers with Pt top contacts supported on conductive zinc tin oxide electrodes with intentionally-oxygenated a-C interfaces. Resistive switching occurs by electron trapping/de-trapping, allowing low power, self-rectifying operation. Broadband light pulses evoke paired-pulse facilitation, emulating photonic coincidence detection. Coincidence detection was also achieved using heterogeneous optoelectronic inputs demonstrating dendritic computation at the single memory cell level. Graphical abstract: Image 1